Stakeholders Mapping Based on Risk of Public Private Partnership (PPP) NonRegional Water Supply Provision in Indonesia - Wardhana, Yuki Mahardhito Adhitya (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
Clean water is a necessity for human life that is obligated to be fulfilled. Quantity and the quality of groundwater are decreasing; thus, water provision through pipelines using the PPP scheme became a flagship option to provide water services, especially in Municipalities. PPP became an option to accelerate clean water provision for non-regional water supply. Water as a necessity has very detailed regulations and complex risks and involves many stakeholders. PPP, risk management, and stakeholders have tight linkages conceptually and through framework. This research aims to map the necessary stakeholders involved in non-regional water supply provision with a risk-based approach to mitigate the risks arising from them. The methodology used in this research is a mixed method using risk identification analysis and stakeholder mapping and identification. The result shows that there are 10 stakeholders in the non-regional PPP water projects, which are split into 3 categories those are key stakeholders, supporting stakeholders, and participating stakeholders. Each stakeholder has the potential to trigger risk in a non-regional PPP water project that sums up to 10 risks. Through this authoritative approach and the relevant support, stakeholders can mitigate the risks that exist in non-regional PPP water projects.